Replicating the Defect Structures on Ultrathin Rh Nanowires with Pt to Achieve Superior Electrocatalytic Activity toward Ethanol Oxidation. (20th November 2018) - Liu, Kai; Wang, Wei; Guo, Penghui; Ye, Jinyu; Wang, Yuanyuan; Li, Pingting; Lyu, Zixi; Geng, Yongsheng; Liu, Maochang; Xie, Shuifen
Abstract: Metal nanostructures with an ultrathin Pt skin and abundant surface defects are attractive for electrocatalytic applications owing to the increased utilization efficiency of Pt atoms and the presence of highly reactive sites. This paper reports a conformal, layer‐by‐layer deposition of Pt atoms on defective Rh nanowires for the faithful replication of surface defects (i.e., grain boundaries) on the Rh nanowires. The thickness of the Pt shell can be controlled from one monolayer up to 5.3 atomic layers. This series of Rh@Pt n L ( n = 1–5.3) core–sheath nanowires show greatly enhanced activity and durability in catalyzing the ethanol oxidation reaction in an acidic medium. Among others, the Rh @ Pt3.5L nanowires show the greatest mass activity (809 mA mg −1 Pt ) and specific activity (1.18 mA cm −2 ) after loaded on carbon support, which are 3.7 and 3.4 times those of the commercial Pt/C, respectively. In situ Fourier transform infrared spectroscopy studies indicate an enhanced interaction between the outermost Pt layer and the Rh nanowire can promote CC bond cleavage for complete oxidation of ethanol to CO2 while depress the dehydrogenation of ethanol to acetic acid. As the Pt shell thickness is increased, the selectivity for the CO2 pathway decreases while that for acetic acid is increased. Abstract : Ultrathin Rh@Pt n L core–sheath nanowires are fabricated through a conformal, layer‐by‐layer deposition of Pt atoms on Rh wavy nanowires with a faithful replication of the surface defects on the Rh nanowires. These Rh@Pt n L nanowires show greatly enhanced activity and durability, and Pt atomic layer dependent selectivity for catalyzing ethanol oxidation in an acidic medium.